2023
DOI: 10.1002/ece3.10512
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of animals is stronger during summer marine heatwaves and around morphologically complex foundation species

Shinae Montie,
Mads S. Thomsen

Abstract: Foundation species create biogenic habitats, modify environmental conditions, augment biodiversity, and control animal community structures. In recent decades, marine heatwaves (MHWs) have affected the ecology of foundation species worldwide, and perhaps also their associated animal communities. However, no realistic field experiment has tested how MHWs affect animals that live in and around these foundation species. We therefore tested, in a four‐factorial field experiment, if colonisation by small mobile mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…Specifically, we found that Ulva attached to Austrovenus enhanced the abundance and richness of invertebrates, but also that the strength of facilitation was stronger in warmer seasons and with higher amount of Ulva , supporting previous research with other foundation species (Ba‐Akdah et al, 2016; Gunnill, 1983; Montie & Thomsen, 2023c; Navarro‐Mayoral et al, 2021; Taylor, 1997; Thomsen et al, 2015, 2022). Perhaps invertebrates were more abundant in warmer summer months because their recruitment and growth typically are faster in this season (Edgar, 1991), as high food availability, reproduction, and metabolism often correlate positively with higher summer temperatures (Ba‐Akdah et al, 2016; Gunnill, 1983; Montie & Thomsen, 2023a, 2023c; Navarro‐Mayoral et al, 2021; Taylor, 1997). Furthermore, invertebrates were likely more common on larger Ulva fronds because large foundation species provide more biogenic habitat and therefore more surface area for more shelter, refugia, and food (Thomsen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we found that Ulva attached to Austrovenus enhanced the abundance and richness of invertebrates, but also that the strength of facilitation was stronger in warmer seasons and with higher amount of Ulva , supporting previous research with other foundation species (Ba‐Akdah et al, 2016; Gunnill, 1983; Montie & Thomsen, 2023c; Navarro‐Mayoral et al, 2021; Taylor, 1997; Thomsen et al, 2015, 2022). Perhaps invertebrates were more abundant in warmer summer months because their recruitment and growth typically are faster in this season (Edgar, 1991), as high food availability, reproduction, and metabolism often correlate positively with higher summer temperatures (Ba‐Akdah et al, 2016; Gunnill, 1983; Montie & Thomsen, 2023a, 2023c; Navarro‐Mayoral et al, 2021; Taylor, 1997). Furthermore, invertebrates were likely more common on larger Ulva fronds because large foundation species provide more biogenic habitat and therefore more surface area for more shelter, refugia, and food (Thomsen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%